2020
DOI: 10.1155/2020/8880661
|View full text |Cite
|
Sign up to set email alerts
|

An Early Warning Method of Distribution System Fault Risk Based on Data Mining

Abstract: Accurate warning information of potential fault risk in the distribution network is essential to the economic operation as well as the rational allocation of maintenance resources. In this paper, we propose a fault risk warning method for a distribution system based on an improved RelieF-Softmax algorithm. Firstly, four categories including 24 fault features of the distribution system are determined through data investigation and preprocessing. Considering the frequency of distribution system faults, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Literature [13] found that because enterprises are in the market competition, there is a great correlation between price fluctuation and audit risk. Literatures [14,15] measured the audit risk with audit fees and found that variables such as accounts receivable level, enterprise assets scale, and number of subsidiaries are significantly correlated with audit risk. In [16], the empirical evidence shows that effective corporate governance can significantly reduce the level of audit risk.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature [13] found that because enterprises are in the market competition, there is a great correlation between price fluctuation and audit risk. Literatures [14,15] measured the audit risk with audit fees and found that variables such as accounts receivable level, enterprise assets scale, and number of subsidiaries are significantly correlated with audit risk. In [16], the empirical evidence shows that effective corporate governance can significantly reduce the level of audit risk.…”
Section: Related Workmentioning
confidence: 99%
“…In formula (1), i represents the sampling sample; j represents the value range of audit early warning features [1,14]; o(x) represents the nearest neighbor sample of the same kind; p(x) represents the nearest neighbor samples of different classes.…”
Section: Application Of Enterprise Financial Audit Early Warningmentioning
confidence: 99%
“…In the charging mode, energy storage absorbs additional power and has load characteristics; in the discharging mode, energy storage releases power to the outside, and at the same time, energy storage can realize rapid power regulation. Energy storage technology can be divided into centralized energy storage and distributed energy storage according to the different access and application methods in the distribution network [2]. Centralized energy storage is mostly used in the occasion of large power and long time.…”
Section: Introductionmentioning
confidence: 99%